Correlation of structure, function and protein dynamics in myoglobins from Eurasian woodcock, chicken and ostrich. Issue 3 (11th February 2021) - Ragucci, Sara; Ruggiero, Alessio; Russo, Rosita; Landi, Nicola; Valletta, Mariangela; Chambery, Angela; Russo, Luigi; Di Maro, Antimo
Abstract: Myoglobin (Mb), oxygen-binding heme-protein retrieved primarily in muscles, is a local oxygen reservoir providing to oxygen when oxygen delivery is insufficient during catabolism. Furthermore, Mb structure is studied as example of molecular evolution for its ability to respond to environmental pressures and adapt to it through few amino acid substitutions. Here, in order to explore the structure–function–dynamics relationships of Eurasian woodcock chicken and ostrich Mbs we have applied an integrated approach in which spectroscopic and biochemical data have been coupled to computational techniques as structural modelling and molecular dynamics simulations. The primary structure of E. woodcock Mb, reveals the presence of 3 (i.e. Q34H, E44D and V66A) and 10 (i.e. A19T, E27A, V28I, K50T, D53E, G57A, D60E, N81K, S84A and A120S) amino acid substitutions respect to chicken and ostrich Mbs, respectively. Although the high amino acid sequence identity, E. woodcock Mb displays a higher autoxidation rate than chicken and ostrich Mb, despite of a similar melting temperature ( T m ∼ 358 K). Yet, the 3D structural models validated by using experimental data indicate that the three Mbs adopt an almost identical three-dimensional structure conserving the typical secondary and tertiary structural organization. Interestingly, dynamics data reveal that the E. woodcock Mb exhibits greater internal motions than either chicken or ostrich Mbs. Overall, our study demonstrates that in Mbs the functional properties are significantly driven by the protein dynamic peculiarities, which in turn depend on the amino acid composition of the region located in proximity of the pathways for the gas ligands. Communicated by Ramaswamy H. Sarma